SINKRONISASI KEGIATAN PERTAMBANGAN PADA KAWASAN HUTAN - I Putu Gede Ardhana (Environmental Research Center (PPLH) of Udayana University, 2009)
This article aims at studying the synchronized activity of the mining industry in forestry zone. This article is composed of normative legal research with the statute approach, the case approach and the library approach which uses the documentes of UKL/UPL and the environmental assessment PLTP in Bedugul made by LIPI and PPLH in Unud, as well as the newses from Walhi magazine and news paper “Bali Post”. From the result of this article we know that controversial application for act No. 11 of 1967 and act No. 41 of 1999 have a difference in the uses of preservational forestry area and conservation for the mining activity in almost forestry area in Indonesia, and with issue of decision letter by ministry of Ekoin No. KEP-04/M.EKON/09/2000 concerning with the coordinating research team for utilizing forestry area to the mining. And the result indicated very cleary that government truely disregardes the safety of preserving and conservative forestry. From reason which occurs problem in this side, we must need to revitalization of legal definity, strong prohibitation to using preservational forestry and conservation from the mining industry. And society must take participation to the establishmental activities from beginning, because society will be able to know the estimation of result faster.